Alone and Together With Myself: How Do We Experience Solitude? (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
Guided by the thinking of Heidegger and Jaspers and understood through my own lived world, this paper seeks to explore and elucidate the human experience of solitude. The relevance to and implications for existential psychotherapeutic practice are considered through the use of clinical examples (names and identifiable details have been changed to protect confidentiality).
Keywords: Solitude; loneliness; alone; pain; creativity; fear; authenticity; tension